Akurasi Estimasi Produksi Susu Test Interval Method sebagai Alternatif Seleksi Sapi Peranakan Friesian Holstein di Area Tropika Basah - Prabowo, S.; Atabany, A.; Komala, I.; Yani, A.; Cyrilla, L.; Murfi, A.; Purwanto, B. P. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2013)
The objective of this research was to assess test interval method for estimation of milk yield of Friesian Holstein Breed in tropical condition for alternative selection in herd. Purposive sampling method was used in this research. Milk yield data were collected base on daily yield from 3 heads lactating cows. Estimated milk yield from test interval method and actual milk yield were analyzed using statistical correlation analysis. The results showed that estimated milk yield significantly correlated (P<0.01) to actual milk yield (r = 0.991). The estimation of milk yield of individual cows was lower or higher than that of their actual milk yield at 305 days never more than that of 0.29 to 0.79 %. It was concluded that test interval methodcould be used accurately to estimate milk yield and in addition could be used for selection of Friesian Holstein Breed in wet tropic area